IMPLICATIONS OF CIVIC EDUCATION FOR THE FORMATION OF STUDENTS’ RELIGIOUS CHARACTER IN THE DIGITAL ERA - Wulandari, Febriyantika; Rahayu, Nina; Restela, Rika; Pertiwi, Asih (Jurnal Asy-Syukriyyah, 2024)
This study explores the influence of civic education on the formation of students’ religious character in the digital era through a Library Research approach. The findings of the literature show that civic education not only acts as a conveyor of knowledge of the rights and obligations of citizens, but also as an initiator of moral values, ethics and religious tolerance which are part of a religious attitude. Social interactions strengthened by civic education shape empathetic attitudes and increase understanding of social diversity. In the digital age, additional complexities arise regarding digital ethics, online responsibility and changes in the dynamics of online social relationships. Thus, this study provides insights into how digital literacy can be integrated into citizenship education to shape adaptive and ethical characters in the digital world.